Credit Risk Management in the Commercial Banking Sector: Reflections from a Historical Comparative Study in Nepal - Aryal, Bharat; Aryal, Arjun; Ghimire, Asmita; Manandhar Bajracharya, Shilu (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Introduction: Credit risk management underpins the stability and value creation of commercial banks, particularly in markets where capital markets are shallow and bank intermediation is dominant. This study provides a historical baseline of credit management in Nepal by comparing two large institutions—anonymised as Bank A (majority state-owned commercial bank) and Bank B (private commercial bank with foreign JV origins)—over FY 2006/07–2010/11. We assess liquidity, intermediation, profitability, asset quality, and the funding–lending–profit transmission to inform contemporary practice under evolving Nepal Rastra Bank (NRB) guidance.Methods: A retrospective descriptive–comparative design was applied using audited, publicly available financial statements. Ratio analysis covered liquidity (e.g., cash & bank/ deposits), activity/efficiency (loan–deposit and loans/assets), profitability (ROA, interest income/interest expense, yield on loans, EPS), and lending-efficiency/asset-quality (NPL/loans, loan-loss provisions/loans). Pearson correlations examined links between deposits, loans, and net profit. Names are anonymised to mitigate legal/ethical risk; all figures are reported exactly as in source tables. Results: Liquidity buffers were higher at Bank A (cash & bank/ deposits 0.216 vs 0.063; cash/current deposits 0.948 vs 0.432; cash/savings 0.368 vs 0.172), while both banks’ current ratios averaged